Vulnerability Assessment of Mangroves in Western Shore of Red Sea - Negm, Nada (AUC Knowledge Fountain, 2024)
Mangroves are vital to environmental sustainability and acts as a global warming control, although they endure severe vulnerability due to some human activities. Climate change and other extrinsic stresses are factors that play a vital role when assessing the vulnerability of mangroves in the Red Sea. The aim of this study is to assess the vulnerability of mangroves using field and RS data to apply a vulnerability index of mangroves at Hamatta and Safaga in Egypt. Mangrove Vulnerability Index covers includes hazard mangrove index, biological mangrove index and physical mangrove index. Mangrove height has been measured using meter tape and tree caliper following Aboulsoud & ElKhouly (2023) method. As for the distance coastline, it has been measured using digital maps and RS images and meter tape using the approach of Kamal et al. (2011). Calculating mangrove canopy density, elevation and NDVI has been concluded using GIS analysis (Griffin et al., 2010; Loi et al., 2017; Singgalen, 2021). Salinity was measured using a TDS meter in Safaga and Hamatta (Aboulsoud et al., 2019). As for the soil geomorphology, it was identified previously by Madkour and Mohamed (2008). Hence, it was used as a secondary source. As for the tidal ranges, it was derived from Maritime Port Sector. Other climate data like wave height and wind speed were retrieved from weather sources like NASA Earth Data and TuTimpe respectively. The average height of A. marina in Safaga is 2.84 m whilst in Hamatta is 2.37 m. The distance to the coastline in Safaga ranges between 20-50 m whilst in Hamatta the distance to the coastline ranges between 30-50 m. Sediments of South Safaga and Hamatta are considered terrigenous sediments. Both sites are categorized as a barrier beach. Red Sea tides are 1.2 -2.1 m. The average elevation of Safaga is 6.7 m while Hamatta is 5.3 m. In Hamatta, the canopy density percentage ranges from 75-88% which is considered a high canopy density and considered in vulnerability as low vulnerability. As for Safaga, the range is between 55-70%. NDVI for both sites indicate that according to their area coverage, they lie between ( -1.000 –0.025). The average salinity in Safaga is 38.7 - 39.4 ppt whilst the salinity in Hamatta is 38.5 - 40 ppt. The annual wind speed in Safaga is 18.1 km/h while in Hamatta is 14.76 km/h as for the wave height it is 0.9-1.2 m. Precipitation is reported to be 0 mm in 2022 during three hours measurement for both sites. Following the Ellison ranking method (2015) the total vulnerability rank of Safaga and Hamatta are considered low in vulnerability. Additional parameters such as water quality, soil quality and came grazing have been considered as local parameters that may directly or indirectly affect mangroves. Both study areas were deducted to be low in vulnerability. This study effectively bridges a significant research gap by providing initial vulnerability assessment of mangroves in Safaga and Hamatta, thereby enhancing our insight of ecological contexts and factors of mangroves in the Egyptian Red Sea